Clinical results of randomized trials and 'real-world' data exploring the impact of Bevacizumab for breast cancer: opportunities for clinical practice and perspectives for research. (3rd April 2017) - Zambonin, Valentina; De Toma, Alessandro; Carbognin, Luisa; Nortilli, Rolando; Fiorio, Elena; Parolin, Veronica; Pilotto, Sara; Cuppone, Federica; Pellini, Francesca; Lombardi, Davide; Pollini, Giovanni Paolo; Tortora, Giampaolo; et al.
ABSTRACT: Introduction : Angiogenesis plays a fundamental role in breast cancer (BC) growth, progression and metastatic spread. After the promising introduction of bevacizumab for the treatment of advanced BC, the initial enthusiasm decreased when the FDA withdrew its approval in 2011. Nevertheless, several clinical studies exploring the role of bevacizumab have been subsequently published. Areas covered : The aim of this study is to review the available clinical trials exploring the potential effectiveness of bevacizumab in BC, regardless of the disease setting. Expert opinion : Even if the evidence suggests that bevacizumab must be ruled out from the HER2-positive and adjuvant setting, bevacizumab's benefit remains uncertain in the neoadjuvant setting and in the advanced treatment of HER2-negative patients. In the first setting, the addition of bevacizumab to chemotherapy increased the pathological complete response (pCR) rate in most clinical trials. However, the current absence of evidence that pCR is a trial-level surrogate for survival requires waiting for long-term results. In the advanced setting, all trials showed a benefit in progression-free survival, but not in overall survival, highlighting an increase of adverse events. The lack of predictors of response represents the main unmet need in which future clinical research will undoubtedly invest.